Development of immortalized Callithrix jacchus kidney cell lines supporting infection with a panel of viruses - Sabine Gärtner; Pamela Stomberg; Stefan Pöhlmann; Michael Winkler (PLoS ONE, 2026)
Common marmosets ( Callithrix jacchus ) are valuable non-human primate (NHP) animal models in biomedical research, including infectious diseases modelling. However, for in vitro studies only a few immortalized cell lines have been generated, and additional lines are needed to comply with the 3R principles of replacement, reduction and refinement. Here, we present the generation and characterization of three cell lines derived from kidney tissue, which were immortalized by transduction of SV40 large T antigen. The cell lines display an epithelioid morphology, show differential podoplanin expression and are likely of pericyte origin, as deduced from expression profiles of marker genes obtained by RNA sequencing analysis (RNA-seq). All cell lines had a functional interferon (IFN) system, as shown by responsiveness to human IFNβ and marmoset IFNα14 and the induction of interferon-stimulated genes (ISG). Infection with retroviral pseudotypes demonstrated susceptibility to entry driven by glycoproteins from a wide range of human pathogenic viruses. Finally, these cell lines are highly permissive for Zika virus, for which marmosets are a model organism, and Herpes simplex virus 1, which causes a deadly disease in marmosets. We believe that these cell lines are a valuable resource for in vitro studies on marmosets.